2015
DOI: 10.17576/gema-2015-1501-02
|View full text |Cite
|
Sign up to set email alerts
|

Examining Acculturation Model in an EFL Context: Learners’ Attitudes towards Target Language Accent vs. L1 Accent

Abstract: According to Schumann"s (1986) Acculturation Model, accent acts as a means of the learner"s identification with either his/her mother tongue culture or the target language culture and affects his/her effort to learn English as a target Language. Taking up a critical stance, the present study, thus, aimed at investigating the role that learner attitudes and beliefs play in the language that learners adopt in their mother tongue (MT) or the target language (TL) (i.e., English) accent when speaking English in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Another possible solution is to ask them to read research papers in academic journals and databases (e.g., Google Scholar or Academia.edu) and note some research questions they can generate from the articles. At some points, if they still find it difficult to find research ideas, we usually guide them to read specific articles that discuss topics in English Language teaching and education, such as motivation (e.g., Al-Tamimi & Shuib, 2009), learning attribution (e.g., Farid & Akhter, 2017), class peer observations (e.g., Nguyen & Ngo, 2018;Vo & Nguyen, 2010), or critical friendships (Farrell, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible solution is to ask them to read research papers in academic journals and databases (e.g., Google Scholar or Academia.edu) and note some research questions they can generate from the articles. At some points, if they still find it difficult to find research ideas, we usually guide them to read specific articles that discuss topics in English Language teaching and education, such as motivation (e.g., Al-Tamimi & Shuib, 2009), learning attribution (e.g., Farid & Akhter, 2017), class peer observations (e.g., Nguyen & Ngo, 2018;Vo & Nguyen, 2010), or critical friendships (Farrell, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the students need to read more published articles to study and borrow some words or phrases presented in those articles. We sometimes provide one or two articles (e.g., Al-Tamimi and Shuib, 2009) for the students and ask them to see vocabulary and phrases that the authors write, for instance, to introduce previous studies or explain the methods of their research.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the participants showed highly positive attitudes towards the target language and its users. Similarly, Al -Tamimi, et al (2009) found that instrumental motivation is behind the learners' positive attitudes towards learning the target language and its use in the social context. Several studies, on the other hand, indicated that most of the participants had a negative attitude towards the target language.…”
Section: Related Studiesmentioning
confidence: 96%
“…English acquisition can guarantee the availability of opportunities for employment, traveling, higher education, and even a better life (Crystal,1997).The students see English as an important tool for obtaining well-paid jobs (Bradford, 2007). Al-Tamimi and Shuib (2009) stated that because of poor performance in English, most university graduates have been rejected by the companies they apply for work. It is indisputable that the impact of globalization and economic development has made English the language of opportunity and a vigorous means of refining an individual's prospects for well-paid employment.…”
Section: Discusion Motivation and Motivational Orientation Of Snem In...mentioning
confidence: 99%